2009
DOI: 10.1063/1.3160732
|View full text |Cite
|
Sign up to set email alerts
|

Particle deposition onto a microsieve

Abstract: The objective of the present work is to investigate experimentally the deposition of micron-sized particles onto the surface of a microsieve membrane, which consists in a thin screen with patterned circular holes. A dilute suspension of spherical, monodisperse, polystyrene particles flows at an imposed flow rate through the membrane, in a frontal filtration mode ͑i.e., the flow direction is perpendicular to the membrane͒. The particle-to-pore diameter ratio is inferior to one. The particle and flow Reynolds nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
34
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 31 publications
0
34
0
Order By: Relevance
“…Simulations with GeoDict software by considering non-adherent surface inside the pores can describe such arches and dense deposit formations in several steps. Initially, particles on critical hydrodynamic trajectories are captured at the entrance channel corners (such an initial particle deposition at a pore corner has already been observed and discussed by Lin et al 2009). Then, particles accumulate in the upstream zone of these first deposited particles or laterally to these particles to form dendrites at the corner of the channel (as seen after 6,000 particles in Fig.…”
Section: Discussionmentioning
confidence: 95%
“…Simulations with GeoDict software by considering non-adherent surface inside the pores can describe such arches and dense deposit formations in several steps. Initially, particles on critical hydrodynamic trajectories are captured at the entrance channel corners (such an initial particle deposition at a pore corner has already been observed and discussed by Lin et al 2009). Then, particles accumulate in the upstream zone of these first deposited particles or laterally to these particles to form dendrites at the corner of the channel (as seen after 6,000 particles in Fig.…”
Section: Discussionmentioning
confidence: 95%
“…For a bi-disperse particle suspension passing through a 5 µm polymer microsieve, Brans et al observed that 1 µm particles are captured at the edges of a circular pore, whereas 10 µm ones deposit exactly on the pore (Brans et al 2007). Using almost the same geometry, Lin et al (2009) also showed that particles smaller than the pore size preferentially deposit close to the pore entrance. Wyss et al (2006) put forward the inertial retardation effect, due to the density difference between the fluid and the particles, to explain the particle deposition on a curved surface at the entrance of the pore.…”
mentioning
confidence: 86%
“…This progressive clogging process remains largely unexplored especially at the pore scale. Recently, several groups have started to address this issue, by looking at the flow of dilute colloidal suspensions within model porous media (microfluidic devices) and microsieves (thin silicon plates patterned withholes) (Wyss et al 2006;Auset and Keller 2006;Baumann and Werth 2004;Brans et al 2007; Kuznar and Elimelech 2007;Lin et al 2009;Bacchin et al 2011). They confirmed the importance of the colloidal forces for the adhesion of the particles on the pore surface, by visualizing the deposition of the first layer of particles on the pore surface.…”
mentioning
confidence: 99%
“…In addition to the bridging mechanism, one can note another process of particle deposition called progressive capture of particles. It means that particles attach one by one either at a preferential position of micropore [16] at the beginning of filtration experiments or onto another adhered particles. This progressive deposition of particles (highlighted during the filtration of particles ; q ¼ 2 ml h À1 Þ. ; q ¼ 2 ml h À1 Þ.…”
Section: à3mentioning
confidence: 99%